Consolidation of sustainable and healthy entrepreneurship based on resonant leadership and labor performance - Chirinos Araque, Yamaru del Valle; Godínez López, Roberto; Barbera Alvarado, Nataliya; Pérez Peralta, Claudia Milena (Revista de Ciencias Sociales, 2022)
The objective of the study is to analyze the consolidation of sustainable and healthy entrepreneurship based on resonant leadership and job performance, with a quantitative approach, descriptive-correlational type; with a transactional field design. The population was made up of 32 subjects from public service companies in Venezuela; the results indicated that the leaders are moderately taking advantage of the capacities and abilities of their employees, which makes it impossible to enhance job performance, generating inconveniences for the achievement of goals and objectives in the organization does not generate an impact on the work performance of workers and prevents these companies from consolidating in sustainable and healthy entrepreneurship.